Enhancing ablation outcomes: vein of Marshall ethanol infusion in persistent atrial fibrillation with severe left atrial enlargement - Luo, Tao; Liu, Tao; Cui, Bo; Deng, Chenggang; Chen, Yanhong; Xiong, Xiong; Zhang, Jinlin; Wu, Gang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundLeft atrial (LA) enlargement is a widely recognized factor that increases the risk of ablation failure in patients with atrial fibrillation (AF). This retrospective, observational study aimed to assess the influence of vein of Marshall (VOM) ethanol infusion (VOM-EI) on persistent atrial fibrillation (PsAF) ablation among patients with severe LA enlargement.MethodsIn this research, 178 patients underwent the VOM-EI followed by the radiofrequency (RF) ablation procedure, which was based on circumferential pulmonary vein antrum (CPVA) ablation and linear ablation of the roof of the LA and the mitral isthmus (MI). In comparison, 83 patients only underwent the RF ablation procedure.ResultsIn the VOM + RF ablation group, the duration of left CPVA ablation was shorter compared to the RF ablation group (20.3 ± 8.7 minutes vs. 27.1 ± 8.1 minutes, P < 0.0001). The rate of MI block was higher (94.9% vs. 85.5%, P = 0.01) in the VOM + RF ablation group, with a shorter MI ablation time (23.2 ± 10.8 minutes vs. 30.5 ± 11.8 minutes, P < 0.0001), and a lower need for coronary sinus vein ablation compared to the RF ablation group (64.0% vs. 78.3%, P = 0.02). Throughout the one-year observation period, the VOM + RF ablation group exhibited a notably superior survival rate without recurrence compared to the RF ablation group (78.7% vs. 65.1%, P = 0.02). As compared to the RF ablation group, the VOM + RF ablation group had a lower rate of recurrence with atrial tachycardia (8.4% vs. 19.3%, P = 0.01).ConclusionThe VOM-EI facilitated the left CPVA and the MI ablation and improved the ablation outcomes in patients with severe LA enlargement for treating PsAF.